Bahasa Inggris - Ahmad Yudha; Alfitri Alfitri; Azwar Azwar; Lucky Zamzami (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2026)
This study explores the conflict between environmental sustainability and community livelihoods at Lake Maninjau, where the expansion of floating net cage aquaculture / keramba jaring apung (KJA) has accelerated environmental degradation. The conservation policy implemented by the Agam Regency government has sparked resistance, particularly in Nagari Koto Malintang, which is the only area to openly oppose the policy. A qualitative descriptive approach was used with purposive sampling to identify eleven informants, including KJA farmers, local officials, and community representatives. Data were gathered through in-depth interviews, field observations, and document analysis, and analyzed using the Miles and Huberman interactive model. The findings show that KJA farmers’ resistance includes violating the ban on expanding KJA, rejecting pollution claims, and engaging in symbolic actions. Drawing on Popkin's theory, this resistance is a rational response to economic dependence and perceived risks from a policy that threatens their livelihoods. In conclusion, KJA farmers' resistance is not simply opposition to ecological goals but a strategic response to protect their livelihoods. This supports Popkin’s view that farmers act based on rational considerations, weighing the policy’s costs and benefits, and the influence of capital owners and political support.